Epiregulin (EREG) and Myocardin Related Transcription Factor A (MRTF-A) Form a Feedforward Loop to Drive Hepatic Stellate Cell Activation - Wu, Xiaoyan; Dong, Wenhui; Zhang, Tianyi; Ren, Haozhen; Wang, Jinglin; Shang, Longcheng; Zhu, Zhengyi; Zhu, Wei; Shi, Xiaolei; Xu, Yong (Frontiers in Cell and Developmental Biology, 2021)
Trans-differentiation of quiescent hepatic stellate cells (HSC) into myofibroblast cells is considered the linchpin of liver fibrosis. A myriad of signaling pathways contribute to HSC activation and consequently liver fibrosis. Epidermal growth factor (EGF) family of cytokines signal through the cognate receptor EGFR to promote HSC activation. In the present study we investigated the transcription regulation of epiregulin (EREG), an EGFR ligand, during HSC activation. We report that EREG expression was significantly up-regulated in activated HSCs compared to quiescent HSCs isolated from mice. In addition, there was an elevation of EREG expression in HSCs undergoing activation in vitro. Of interest, deficiency of myocardin-related transcription factor A (MRTF-A), a well-documented regulator of HSC trans-differentiation, attenuated up-regulation of EREG expression both in vivo and in vitro. Further analysis revealed that MRTF-A interacted with serum response factor (SRF) to bind directly to the EREG promoter and activate EREG transcription. EREG treatment promoted HSC activation in vitro, which was blocked by MRTF-A depletion or inhibition. Mechanistically, EREG stimulated nuclear trans-location of MRTF-A in HSCs. Together, our data portray an EREG-MRTF-A feedback loop that contributes to HSC activation and suggest that targeting the EREG-MRTF-A axis may yield therapeutic solutions against liver fibrosis.